2021
DOI: 10.1038/s41396-021-01138-y
|View full text |Cite
|
Sign up to set email alerts
|

The fungal root endophyte Serendipita vermifera displays inter-kingdom synergistic beneficial effects with the microbiota in Arabidopsis thaliana and barley

Abstract: Plant root-associated bacteria can confer protection against pathogen infection. By contrast, the beneficial effects of root endophytic fungi and their synergistic interactions with bacteria remain poorly defined. We demonstrate that the combined action of a fungal root endophyte from a widespread taxon with core bacterial microbiota members provides synergistic protection against an aggressive soil-borne pathogen in Arabidopsis thaliana and barley. We additionally reveal early inter-kingdom growth promotion b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 96 publications
1
34
0
Order By: Relevance
“…An alternative, and not mutually exclusive, scenario is that disease resistance may have been the trait under agronomic selection. This would be in line with a recent investigation which demonstrated that bacteria isolated from the barley rhizosphere mediated the establishment of both pathogenic and mutualistic fungi in roots 73 . In this scenario, selection at QRMC-3HS may contribute to the fine-tuning of these multitrophic interactions.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…An alternative, and not mutually exclusive, scenario is that disease resistance may have been the trait under agronomic selection. This would be in line with a recent investigation which demonstrated that bacteria isolated from the barley rhizosphere mediated the establishment of both pathogenic and mutualistic fungi in roots 73 . In this scenario, selection at QRMC-3HS may contribute to the fine-tuning of these multitrophic interactions.…”
Section: Discussionsupporting
confidence: 88%
“…The copyright holder for this preprint this version posted December 21, 2021. ; https://doi.org/10.1101/2021.12.20.472907 doi: bioRxiv preprint demonstrated that bacteria isolated from the barley rhizosphere mediated the establishment of both pathogenic and mutualistic fungi in roots 71 . In this scenario, selection at QRMC-3HS may contribute to the fine-tuning of these multitrophic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Under current global change scenarios, the abundance of plant pathogens in soil is predicted to increase (Delgado‐Baquerizo et al ., 2020), implying that plant protection by endophytic mycorrhizal‐like fungi could improve plant adaptation to increased disease pressure. Serendipita indica has been shown to promote plant resistance by modulating plant defences, but also by interacting with various rhizosphere bacteria acting through microbial processes involving lytic enzymes (Mahdi et al ., 2021). Similarly, H. chaetospira induces plant defence and has been described as a plant protection agent (Lahlali et al ., 2014).…”
Section: Will Mycorrhiza‐like Associations Help Plants Adapt To Globa...mentioning
confidence: 99%
“…Recently, we described a soluble extracellular β-glucan matrix produced by endophytic fungi during root colonization of Arabidopsis thaliana (hereafter Arabidopsis) and Hordeum vulgare (hereafter barley; Wawra et al, 2019 ). Little is known about the biochemical properties, composition, and function of this EPS matrix, but its detection in beneficial and pathogenic fungi strongly suggests a conserved role in counteracting environmental and immunological challenges during fungal growth and plant colonization ( El Oirdi et al, 2011 ; Mahdi et al, 2021 ; Wanke et al, 2021 ). It is therefore crucial to investigate the structure and function of these soluble β-glucans and the hydrolytic events mediated by host apoplastic CAZymes during plant–fungal interactions.…”
Section: Introductionmentioning
confidence: 99%